Analyzing the Physical and Infrastructural Resilience to Fire Accidents in District 20 of Tehran, Iran, Based on the Geographic Information System - Eslam Ali Khodabandehlou; Amir Hooman Hemmasi; Akramolmoluk Lahijanian; Amir Hesam Hassani; Ali Mohammadi (دانش پیشگیری و مدیریت بحران)
Background and objective The present study aims to analyze the status of physical and infrastructural resilience to fire accidents in District 20 of Tehran, Iran based on the geographic information system. Method First, the criteria to evaluate the physical and infrastructural resilience were collected. Then, researcher-made questionnaires were completed by 15 experts from fire departments in Tehran, to rate the importance of these criteria. The weight of these factors was calculated using the Expert Choice 11 software. By layering the criteria using the weights obtained from the analytical hierarchical process (AHP) in ArcGIS software, version 10.6 and overlaying the layers, the final resilience map of District 20 was prepared. Results There were three main criteria, seven sub-criteria, and 21 indicators to evaluate the resilience. Based on the software output, the main criteria were prioritized as infrastructure resilience with a weight of 0.731, physical resilience with a weight of 0.188, and environmental resilience with a weight of 0.081. Based on the zoning map of resilience in the context of health, safety, and environment, it was found that 3.3% of the area (729,718 m2) had low resilience, 35.38% (7,802,578 m2) moderate resilience, 29.54% (6,513,646 m2) high resilience, 30.1% (6,639,824 m2) very high resilience, and 1.65% (364,196 m2) extremely high resilience. Conclusion According to the results, the District 20 of Tehran has appropriate physical and infrastructural resilience to fire and accidents.